New international commentary on the Old Testament : The book of Numbers - Ashley, Timothy R., 1947- (Grand Rapids, Mich. : Eerdmans, 1993)
Ashley's study on the book of Numbers is part of The New International Commentary on the Old Testament. Like its companion series on the New Testament, this commentary devotes considerable care to achieving a balance between technical information and homiletic-devotional interpretation.
**The book of Numbers tells a story that has two main characters God and Israel. The way the story is told sounds odd and often harsh to readers today. In spite of the difficulties imposed by Numbers on todays readers, the main point of the book is of immense importance for Gods people in any age: exact obedience to God is crucial.
Dividing the text of Numbers into five major sections, Ashleys commentary elucidates the theological themes of obedience and disobedience that run throughout the books narrative. His detailed verse-by-verse comments are intended primarily to explain the Hebrew text of Numbers as we have it rather than to speculate on how the book came to be in its present form.
Title and contents -- Structure -- Authorship and Composition -- Theological themes -- Text and versions -- Analysis of contents -- Select bibliography -- Preparation for departure (1:1-10:10) -- The journey from Mt. Sinai to Kadesh-barnea (10:11-12:16) -- In and around Kadesh-barnea (13:1-19:22) -- The journey from Kadesh-barnea to the plains of Moab (20:1-22:1) -- On the plains of Moab (22:2-36:13)
Includes bibliographical references (pages 17-40) and indexes.
Keywords: Bible. -- Commentaries; Commentaries